Lake Sevan modeling data 2008- 2017 including inflows, outflow, temperature and model setup - Muhammed Shikhani; Chenxi Mi; Artur Gevorgyan; Gor Gevorgyan; Amalya Misakyan; Levon Azizyan; Klemens Barfus; Martin Schulze; Tom Shatwell; Karsten Rinke (PANGAEA, 2023)
This dataset is regarding the modeling work of Lake Sevan, the largest freshwater lake in the Caucasus titled (Shikhani et al., Simulating thermal dynamics of the largest lake in the Caucasus region: The mountain Lake Sevan). This data was used to drive the General Lake Model, calibrate the model, and validate it. It contains the inflows, the outflow, the lake bathymetry, water level observations, and the meteorology (average of observed stations), as well as the temperature profiles in both of the sampling points. Moreover, it contains the nml file of the settings of the GLM used for this manuscript. Between 2008 and 2017.